Comparison of the Effect of Induction of General Anesthesia with Propofol Vs Ketamine + Midazolam on Perfusion Index in Cardiac Patients Undergoing Non-Cardiac Surgery: General Anesthesia with Propofol Vs Ketamine + Midazolam on Perfusion Index in Cardiac Patients - Khan, Muhammad Ashraf; Afzal, Farrukh; Yousaf, Sohaib; Bashir, Sheeza; Aslam, Sundas; Farooq, Majid; Mehran, Hafiz Muhammad Umer (Pakistan Journal of Health Sciences, 2026)
Hemodynamic stability is a critical concern in cardiac patients. The choice of induction agent significantly influences cardiac output and tissue perfusion. Objectives: To compare the effect of induction with ketamine and midazolam vs. propofol on perfusion index in cardiac patients under general anesthesia. Methods: This quasi-experimental study was done from January 2024 to June 2024 at the Department of Anesthesia, Mayo Hospital, Lahore. Total 146 patients undergoing non-cardiac surgery were included after taking written consent. Patients were assigned to two equal Groups: M (midazolam and ketamine) or Group P (propofol). Outcome parameters, including SBP, MAP, and perfusion index, were recorded pre- and post-induction. Data were collected using a proforma and analyzed with SPSS-26. Results: Post-induction, mean SBP in Group M was higher, 126.02 ± 12.58 mmHg, vs Group P, 120.61 ± 13.09 mmHg, p-value=0.01. Post-induction mean MAP in Group M and P calculated was 74.17 ± 10.06 mmHg, and 71.02 ± 9.82 mmHg, p-value=0.05. Post-induction PI in Group M was also higher, 1.88 ± 0.40, vs Group P, 1.69 ± 0.28, p-value=0.001. Conclusions: Findings of the current study suggest that induction with ketamine and midazolam may lead to increased post-induction mean perfusion index as compared to propofol in cardiac patients. Therefore, assists in maintaining peripheral perfusion in cardiac patients, which could be beneficial for postoperative recovery and minimizing complications.